The transatlantic Las Casas historical trajectories, indigenous cultures, scholastic thought, and reception in history - Roldán-Figueroa, Rady 1972-; Orique, David Thomas 1959- (Leiden Boston Brill, 2023)
"The Transatlantic Las Casas demonstrates the vitality of Lascasian studies. An impressive ensemble of scholars spanning the fields of Latin American studies, philosophy, theology, anthropology, law, literary criticism, and ethnohistory illuminate the complex intellectual web surrounding this controversial figure. This volume offers sophisticated explorations of colonial Latin American and early modern Iberian studies in a single volume from Laura Ammon; Thomas Eggensperger O.P.; Natsuko Matsumori; Timothy A. McCallister; Luis Mora Rodríguez; David Thomas Orique, O.P.; María Cristina Ríos Espinosa; Rady Roldán-Figueroa; Mario Ruíz Sotelo; Frauke Sachse; Rubén A. Sánchez-Godoy; John F. Schwaller; Garry Sparks; Vanina M. Teglia; Dwight E.R. TenHuisen; Paola Uparela; Ramón Darío Valdivia Giménez; Andrew L. Wilson, and Victor Zorrilla"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Casas, Bartolomé de las -- 1484-1566 -- Influence; Casas, Bartolomé de las -- 1484-1566 -- Philosophy; Indians, Treatment of -- New Spain -- History -- 16th century; Church work with Indians -- Catholic Church; Evangelistic work -- Latin America -- History -- 16th century; Missionaries -- Spain -- Biography; Scholasticism -- Latin America; Latin America -- Intellectual life -- History -- 16th century; New Spain -- Intellectual life; Aufsatzsammlung